Inventarisasi Mangrove Di Kawasan Hutan Mangrove Cagar Alam Pulau Dua - Reza Amalia; Indria Wahyuni; meliyana Meliyana; Ranisah Ranisah; Riesta Octovian; Siti Eliyana (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
Mangrove forest is a forest with a pattern shape that is influenced by the presence of tides, with anaerobic soil conditions. Mangrove forests are a group of plants consisting of various types of plants from different families, but have the same morphological and physiological adaptability to habitats affected by tides. The purpose of this study is to inventory and find out the types of plants in the Pulau Dua Serang Nature Reserve Area. The method used in this study is direct exploration with exploration, identification, literature, and documentation. The data analysis carried out in this study was in the form of descriptive qualitative, namely sampling, data collection, documentation, and identification of plant species. The results showed that 20 species of mangroves were found consisting of 15 true mangrove species and 5 associated mangrove species found in the Pulau Dua Nature Reserve Area, Serang City.